Kepentingan Golongan Tekno-Dai dalam Penyebaran Dakwah - Abd. Ghani, Zulkiple (Jurnal Usuluddin, 2004)
This paper seeks to discuss the importance of a group of techno-da i in the diffusion of da wah message. As there is a close affinity between the technology and the duty of da wah, the emergence of professional techno da i must be planned and well-trained. Some challenges and examples on operating the media by Muslims are carefully examined in this paper. It has been argued that rapid technological change has placed a lot of pressures to establish techno-da i who can mobilise and shape the minds of Muslim audiences as ordered in Islam.